Slow magnetic relaxation and water oxidation activity of dinuclear CoIICoIII and unique triangular CoIICoIICoIII mixed-valence complexes. Issue 19 (28th April 2020) - Modak, Ritwik; Mondal, Biswajit; Sikdar, Yeasin; Banerjee, Jayisha; Colacio, Enrique; Oyarzabal, Itziar; Cano, Joan; Goswami, Sanchita
Abstract : Mixed valence cobalt based coordination compounds acting as single ion magnets and water oxidation catalysts. Abstract : Construction of efficient multifunctional materials is one of the greatest challenges of our time. We herein report the magnetic and catalytic characterization of dinuclear [Co III Co II (HL 1 )2 (EtOH)(H2 O)]Cl·2H2 O (1 ) and trinuclear [Co III CoII2(HL 2 )2 (L 2 )Cl2 ]·3H2 O (2 ) mixed valence complexes. Relevant structural features of the complexes have been mentioned to correlate with their magnetic and catalytic properties. Unique structural features, especially in terms of significant distortions around the Co II centre(s), prompted us to test both spin–orbit coupling (SOC) and zero field splitting (ZFS) methodologies for the systems. The positive sign of D values has been established from X-band EPR spectra recorded in the 5–40 K temperature range and reaffirmed by CAS/NEVPT2 calculations. ZFS tensors are also extracted for the compounds along with Co II Ga III and Co II Zn II Co III model species. Interestingly, 1 shows slow relaxation of magnetization below 6.5 K in the presence of a 1000 Oe external dc field with two relaxation processes ( U eff = 37.0 K with τ 0 = 1.57 × 10 −8 s for the SR process and U eff = 7 K with τ 0 = 1.66 × 10 −6 s for the FR process). As mixed valence cobalt complexes with various nuclearities are central to the quest for water oxidation catalysts, we were prompted to explore their features and to our surprise, water oxidation ability has been realized for both 1 and 2 with significant nuclearity control.